Survivability and behavior of probiotic bacteria encapsulated by internal gelation in non-dairy matrix and In Vitro GIT conditions. - Safdar Nazir; Muhammad Afzaal; Farhan Saeed; Aftab Ahmad; Huda Ateeq; Ali Ikram; Amara Rasheed; Faiza Kiran; Noor Akram; Faiyaz Ahmed; Aasma Asghar; Mahbubur Rahman Khan (PLoS ONE)
The primary objective of this investigation was to assess the viability of free and encapsulated Lactobacillus plantarum probiotics in mango juice and under simulated gastrointestinal conditions. Specifically, the probiotics were encapsulated using sodium alginate and alginate-soy protein isolate through the internal gelation method, and the obtained probiotics were characterized for various attributes. Both free and encapsulated probiotics were exposed to challenging conditions, including thermal stress, low temperature, and simulated gastrointestinal conditions. Additionally, both types of probiotics were incorporated into mango juice, and their survival was monitored over a 28-day storage period. Following viability under simulated gastrointestinal conditions, the count of free and encapsulated probiotic cells decreased from initial levels of 9.57 log CFU/mL, 9.55 log CFU/mL, and 9.53 log CFU/mL, 9.56 log CFU/mL to final levels of 6.14 log CFU/mL, 8.31 log CFU/mL, and 6.24 log CFU/mL, 8.62 log CFU/mL, respectively. Notably, encapsulated probiotics exhibited a decrease of 1.24 log CFU and 0.94 log CFU, while free cells experienced a reduction of 3.43 log CFU and 6.24 log CFU in mango juice over the storage period. Encapsulated probiotics demonstrated higher viability in mango juice compared to free probiotics throughout the 28-day storage period. These findings suggest that mango juice can be enriched with probiotics to create a health-promoting beverage.